Analysis of the modern nature of bankruptcy institution in the Russian Federation - L. A. Mostovaya; S. A. Antonov (Вестник университета, 2025)
The purposes of this article are to reasonably determine the nature of the institution of bankruptcy and assess its impact on law enforcement practice.   The basic methods of the article are: historical review, substantive (content) analysis, causal analysis, statistical (horizontal and vertical) research of data on bankruptcy procedures, observation of consequences.   Methodologically, the work is based on a brief description of historical milestones in the development of the institute of bankruptcy and on the analysis of the transformation of understanding the essence of the concept of insolvency in various editions of the Federal law. Then causal relationships are established, reflecting the key changes in the current Federal law No. 127 of October 26, 2002 and a hypothesis is expressed about the liquidation nature of the institution. Using open statistical data from official bodies and current research by specialists on the subject of the article, the authors reasonably confirm the initial hypothesis (quantitative characteristics are given). The work is completed with an assessment of the impact of the liquidation nature of the bankruptcy institution on the law enforcement practice and the negative consequences of this state of affairs are revealed, which necessitates (determines the expediency) an additional study of the causes. The main results of the article can be applied in the practice of teaching such disciplines as anti-crisis management, legal foundations of insolvency (bankruptcy), arbitration process. A fairly clear justification of the nature and consequences of the functioning of the modern institution of bankruptcy can be considered a contribution to science. Practical usefulness is manifested in the indication of weak points of the legislation that are applied for the purpose of unfair enrichment.